Neuroprotective properties of Na+/H+-exchanger isoform-1 inhibitor in experimental POAG - Anna S. Pobeda; Alexander A. Spasov; Olga N. Zhukovskaya; Kristina V. Shchurovskaya; Nikolai V. Solovev; Valentina A. Kulikovskaya; Vladimir M. Pokrovsky; Evgeny A. Patrakhanov; Anastasia V. Turpakova; Anna I. Ustinova (Belgorod National Research University, 2023)
Introduction: Worldwide glaucoma is the leading cause of irreversible vision loss. The processes associated with the loss of retinal ganglion cells are multifactorial and have much in common with neurodegenerative diseases. Therefore the search for means to prevent the death of retinal neurons is an important task of modern pharmacology. Materials and Methods: The study was conducted on male Wistar rats. Glaucoma was modeled by injecting a 1% solution of hyaluronic acid into the anterior chamber of the eye. The IOP level was recorded on the 0th, 63rd and 73rd days of the experiment. The effectiveness of the drugs was evaluated based on the results of ophthalmoscopy, electroretinography, followed by the determination of gene expression. Results and Discussion: In the group with RU-1355 correction, the fundus picture improved; the index in the group was 18.0% lower compared to the model. The introduction of the RU-1355 compound provided an increase in the a-wave amplitude by 18.1%, and b-wave amplitude by 39.0% relative to the group with pathology. The most pronounced effect was observed on the expression level of BDNF, Bcl-2, Caspase 3 and NF-κB p65, which indicates that the compound has the capacity to influence the slowdown of the apoptosis process through an increase in the neurotrophic factor and the anti-apoptotic factor Bcl-2. Conclusion: RU-1355 has neuroprotective properties, which was expressed by a decrease in ophthalmoscopic manifestations, preservation of the b-wave amplitude of the electroretinogram and the influence on gene expression of factors involved in apoptosis and neuroprotection. Based on the pharmacological activity of the RU-1355 compound in relation to POAG, further study of its action against other retinal diseases is promising.